The Implementation of Field Trips as Edu-Tourism to Improve Students’ Speaking Ability at University Level - Harahap, Dina Irmayanti; Firdaus, Firdayanti (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2020)
Field trip programs as edu-tourism in university level were viewed as the great equalizer in terms of delivering students to cultural heritage awareness. So, they had seen these experiential learning as a central of educational mission. Higher level education especially university which implemented field trip programs as supporting activities in the English for tourism lesson was gladly endured the expense and disruption of providing field trips as the primary purpose to provide a learning opportunity. The aim of this study was to evaluate the implementation of educational field trips as edu-tourism at university level. This is a qualitative study which is carried out by survey and observation. The population of this study is the English Department students of Potensi Utama University. There were 150 respondents in this research which included of 50 teachers and 100 students were randomly selected. The instrument of this study used questionnaires and speaking test items. The questionnaire consisted of 30 items. The collection of in this research were analysed by using simple percentage method. The place for field trip activity was held in the ecotourism of Bukit Lawang, which located at Bahorok sub-district, Langkat Regency, North Sumatera, Indonesia. The result of this study hoped that educational field trips are helpful to cope up with advance learning to develop students’ interest especially speaking ability.